Measuring the Impact of MiFID II on Information Asymmetries Using Microstructure Models - Erik-Jan Senn (Junior Management Science (JUMS), 2020)
This paper evaluates the impact of the Markets in Financial Instruments Directive II (MiFID II) regulation on information asymmetries. The microstructure models of Madhavan et al. (1997) and Glosten and Harris (1988) are adapted to estimate potential changes in the adverse selection component of the spread. I use trade and quote data of 50 German stocks traded at the Cboe Europe Equities exchange. To classify trades in presence of uncertainly about the sequence of trades and quotes within a second, a robust classification method is developed. I find a short-term increase in adverse selection and transaction cost after the MiFID II implementation. A long-term reduction of information asymmetries due to the regulation is indicated and discussed.
Keywords: 650; Market Microstructure; MiFID II / Markets in Financial Instruments Directive II; Information Asymmetry in Limit Order Books; Trade Classification; Financial Market Regulation